Perancangan UI dan UX pada Aplikasi Pencari Homestay di Labuan Bajo - Mariano Charlos Patiatma; I Wayan Santiyasa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Labuan Bajo is one of the popular tourist destinations in Indonesia. With the significant growth in the number of tourists, the need for homestays or local accommodation is increasing. However, tourists often have difficulty finding a homestay that suits their preferences, both in terms of price,facilities or location. This research aims to develop an Android-based homestay application that can help tourists find a homestay that suits their preferences. This application was developed using prototyping and modeling methods. The research results show that an Androidbased homestay application can help tourists find a homestay that suits their preferences. This application has features such as searching for the nearest homestay, rating filters, prices and desired facilities. This application can be a solution for tourists who want to find a homestay that suits their needs. This application can also help homestay managers to promote their homestays to tourists.